SCHOTTKY DIODE CHARACTERISTICS AND DEEP LEVELS ON HYDROGENATED N-TYPE GAAS - KIM, EK; CHO, HY; KIM, HS; MIN, SK; KIM, T (IOP PUBLISHING LTD, 1992)
Schottky diode characteristics and deep levels of Si-doped n-type GaAs after hydrogen plasma exposure have been investigated as a function of substrate temperature during hydrogenation. The barrier height and reverse breakdown voltage of Au Schottky diodes on Si-doped GaAs increased during hydrogen plasma exposure. The ideality factor of the hydrogenated samples was lowered to 1.11 at substrate temperatures between 150 and 250-degrees-C, and deep levels in these samples were effectively passivated at these temperatures. These properties of n-GaAs can be related to hydrogen redistribution in an electrically passivated surface layer. Good diode characteristics and the most effective passivation of deep levels in GaAs could be achieved at a substrate temperature of about 200-degrees-C and a power density of 0.06 W cm-2.
Keywords: GROWN GAAS; HB-GAAS; PASSIVATION; BARRIERS; ELECTRON; EL2